Nutrient Management for Sustainable Dryland Farming Systems - Halvorson, Ardell D; Havlin, John L; Schlegel, Alan J (Annals of Arid Zone, 2016)
Managing nutrients in sustainable dry land fanning systems requires evaluation of all factors limiting’ crop yield potential before plant nutrients are applied. In semi-arid areas, plant-available water is generally the major factor limiting yield, followed by N and P fertility. Adoption of minimum-till (Mf) and no-till (NT) crop production systems increase soil storage of precipitation during non-crop periods, enabling more intensive cropping (2 crops in 3 years, 3 crops in 4 years, or annual cropping). As cropping intensity increases, so does the .need for additional plant nutrients. Soil testing and plant analysis are essential tools for managing crop nutrients in environmentally sound, sustainable fanning systems.Banding of nutrients close to the seed at planting will improve nutrient-use efficiency, particularly in MT and NT systems. Precision fanning technologies are being developed to apply variable rates of fertilizer across fields rather than a single rate. In addition, seeding equipment is now available to allow one pass variable rate seeding and fertilization with fertilizer placed with tile seed, between seed rows, or in bands near tile seed. Reduced tillage systems, combined With more intensive cropping andÂ· variable rate fertilizer applications, are contributing to a more sustainable dryland fanning system in semi-arid areas of tile North American Great Plains.